1990
DOI: 10.1139/g90-075
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of supernumerary spikelets in a tetraploid wheat cross

Abstract: The supernumerary spikelet (SS) trait of durum wheat (Triticum turgidum L.), including the four-rowed and ramified spike types, is characterized by an increased number of spikelets per spike. To determine the inheritance of this trait, the tetraploid ramified spike cultivar PI349056 was crossed reciprocally to normal-spike 'Langdon' durum, and the F1 was backcrossed to each parent. The F1, F2, F3, BC1F1, and BC1F2 were classified for SS expression. Additionally, PI349056 was crossed to the 'Langdon' 2D(2A) dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 7 publications
2
18
0
1
Order By: Relevance
“…S1). In tetraploid and hexaploid wheat species, the development of SS is a recessive trait (Pennell and Halloran, 1983;Klindworth et al, 1990b;Dobrovolskaya et al, 2009) and Figure 1. SS phenotypes in bread wheat.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S1). In tetraploid and hexaploid wheat species, the development of SS is a recessive trait (Pennell and Halloran, 1983;Klindworth et al, 1990b;Dobrovolskaya et al, 2009) and Figure 1. SS phenotypes in bread wheat.…”
mentioning
confidence: 99%
“…es 2nd , Ectopic spikelet of the is modulated by a number of environmental factors (Sharman, 1944;Pennell and Halloran, 1983). In tetraploid wheat (genome nomenclature, BBAA), the SS trait is quantitatively inherited, controlled by a single major gene acting in concert with an unknown number of minor genes (Klindworth et al, 1990b;Haque et al, 2012). It has been suggested that the SS trait in hexaploid wheat (BBAADD) is determined by either two (Pennell and Halloran, 1983) or three (Koric, 1980) loci.…”
mentioning
confidence: 99%
“…Some of studies found that the multiple spikelet might be dominant or partially dominant trait inheritance controlled by one or two genes (Sun et al, 2009;Sun et al, 2000;Chapman and McNeal, 1971;Dencic, 1988). Also some studies found that multiple spikelet traits could be quantitative inheritance, usually jointly controlled by a major gene and several minor genes (Zheng, 1994a;1994b;Klindworth et al, 1990a;1990b;Millet, 1987). Previous studies on chromosome analysis by using monomer and nullisome of Chinese Spring had some multiple spikelet gene mapped on the chromosomes of 2A, 4A, 5A, 7A, 2B, 4B, 2D, 3D and 6D (Peng et al, 1998a;1998b;Zheng et al, 1994b;Yen et al, 1995), of which there was a strong genetic effect on the chromosome 2D (Peng et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…Dobrovolskaya et al (2009) mapped the mrs gene on chromosome 2DS using microsatellite markers. In wheat, the supernumerary spikelets trait is recessive (Pennell and Halloran 1983;Klindworth et al 1990a;Peng et al 1998;Martinek and Bednář 2001). The expression of the trait is modulated by a number of environmental factors (Sharman 1944;Pennell and Halloran 1983).…”
Section: Introductionmentioning
confidence: 99%